Breast tumor tissue inflammation but not lobular involution is associated with survival among breast cancer patients in the Multiethnic Cohort. (April 2020) - Maskarinec, Gertraud; Ju, Dan; Shvetsov, Yurii B.; Horio, David; Chan, Owen; Loo, Lenora W.M.; Hernandez, Brenda Y.
Highlights: Little is known about the influence of the tissue-specific characteristics with survival among women diagnosed with breast cancer. This study examined breast lobular involution and three inflammatory markers as predictors of breast cancer survival in the Multiethnic Cohort. Strong expression of inflammatory markers but not involution in breast tissue predicted a poorer prognosis among women with breast cancer. Addressing underlying causes of chronic inflammation in breast cancer patients may help to improve overall health and life expectancy. Abstract: Background: This study investigated the association of breast lobular involution status and three inflammatory markers as predictors of survival among breast cancer patients in the Multiethnic Cohort. Methods: Lobular involution was evaluated in tissue sections of normal breast tissue and COX-2, TNF-α, and TGF-β proteins were assessed by immunohistochemistry in tumor microarrays. A summary score added the expression levels of the three markers. Cox regression was applied to estimate hazard ratios (HRs) and 95 % confidence intervals (CI) with age as the time metric and adjustment for factors known to affect mortality. Results: Among 254 women (mean age = 61.7 ± 8.7 years) with pathologic blocks and follow-up information, 54 all-cause and 10 breast cancer-specific deaths were identified after a mean follow-up time of 16.0 ± 3.1 years. For 214 participants, an inflammatory score was available and 157 women had information on lobular involution. Lobular involution was not significantly associated with survival. Expression of both COX-2 and TNF-α were significant predictors of lower survival (p = 0.02 and 0.04), while the association for TGF-β was weaker (p = 0.09). When combined into one overall inflammation score, both intermediate (HR = 2.72; 95 % CI 0.90–8.28) and high (HR = 4.21; 95 % CI 1.51–11.8) scores were associated with higher mortality but only the latter was statistically significant. No significant association with breast cancer-specific mortality was detected. Conclusions: These results suggest that strong expression of inflammatory markers in breast tissue predicts a poorer prognosis possibly due to a system-wide state of chronic inflammation.